Elevated cortisol in healthy female adolescent offspring of mothers with posttraumatic stress disorder. (May 2016) - Liu, Keke; Ruggero, Camilo J.; Goldstein, Brandon; Klein, Daniel N.; Perlman, Greg; Broderick, Joan; Kotov, Roman
Highlights: Cortisol awakening response was measured in healthy adolescents with maternal PTSD. Maternal PTSD is associated with higher cortisol in healthy adolescent offspring. Altered cortisol may represent a vulnerability factor for PTSD in at-risk youth. Abstract: Offspring with maternal PTSD are at increased risk of developing PTSD themselves. Alterations in the hypothalamic-pituitary-adrenal (HPA) axis may play a role and have been noted in offspring, although evidence is mostly from adult offspring with PTSD symptoms themselves. The present study of adolescent girls ( N  = 472) and their mothers ( n  = 18 with lifetime PTSD versus n  = 454 with no PTSD) sought to determine whether healthy, non-affected offspring of mothers with PTSD would exhibit altered HPA axis function. Saliva samples were collected from the adolescent girls at waking, 30 min after waking, and 8 pm on 3 consecutive days. Offspring whose mothers were diagnosed with PTSD demonstrated higher cortisol awakening response (CAR; Cohen's d  = 0.58) and greater total cortisol output (Cohen's d  = 0.62). In this preliminary study, higher cortisol levels during adolescence among offspring of mothers with PTSD may index a vulnerability in these at-risk youth.